The impact of intellectual Capital on Educational Institutions Profitability - Sabra, Samar Tawfiq (Journal of Economic, Administrative and Legal Sciences, 2018)
The study aimed at measuring the impact of intellectual capital on increasing the profitability of)Al Quds College, Al Khwarizmi College, Hittin College, Arab Community College, Qadisiya College(. To achieve the research objective, a questionnaire was prepared according to study hypotheses. The study population consisted of all academics, managers, department heads and technicians in the selected colleges. A random sample of 150 respondents was selected. The study used analytical descriptive method.. The study concluded that intellectual capital (human capital, structural capital, relational capital, intellectual assets capital) to increase the profitability of (Al-Quds College, Al-Khwarizmi College, Hittin College, Arab Community College, Qadisiyah College). Based on the findings, the study recommended that educational institutions have to pay attention to intellectual capital and maintain its assets due to its significant role in increasing colleges profitability.